THE EFFECT OF THE INTERMEDIATE DISTANCE BETWEEN THE WORKING PARTS OF THE CLEANING MACHINE ON THE DEGREE OF CLEANING - Mirzabayev Jamoliddin Bahriddinovich (Western European Studies, 2024)
In this article, the influence of the distance between the working parts of cotton ginning machines on the level of cleaning is studied. According to the study of the separating blade profiles, studies were conducted on the use of a perforated surface for the cleaning part. The structure, shape and cleaning process of the working parts of the cleaning machines used in the spinning enterprises and the experiments conducted on a smooth surface with different diameters of perforations are presented
Keywords: cleaning; perforated surface; spacing; pressure